A modified advanced encryption standard based on lora for monitoring and protecting distributed systems - Vineeth Vellora Veetil; Sophia Sudhir (Ain Shams Engineering Journal)
The development of a smart grid in the power system depends heavily on efficient energy consumption. Therefore, a top priority of smart grid (SM) is accurate monitoring and management of energy use. A smart power grid is a system of two-way communication where exchange of data is crucial to the transmission and distribution of electricity. In contrast to a conventional energy meter, SM is an enhanced energy meter that facilitates two-way communications. To support decentralized generation sources and energy storage devices, it is able to measure consumer’s energy usage and subsequently relay additional information to utility providers. The act of collecting utility meter evaluations from electricity and recognizing unlicensed utilization of power is challenging and time-consuming which requires human resources in majority for underdeveloped countries. Internet of Things (IoT) presents an efficient and inexpensive method of wirelessly transferring information on energy utilized by consumer and features to identify unauthorized use of electricity. The purpose of this work is to employ IoT and telemetric communication methods to monitor residential usage of electricity and automatically produce a bill. This work also attempts to identify and reduce energy theft. The digital energy meter system is controlled by an Arduino microcontroller, which additionally serves to connect the device to a LORA (Long Range) network, then to the server and Internet. The technology uses improved Advanced Encryption Standard (I-AES) to identify any unauthorized changes made to metering system. In such an instance, system has the abilities to automatically cut and reconnect the electricity supply while also sending a notification to server. Using a network of IoT, energy consumptions are computed on its own, and the bill is modified online. The demand for manual work may decline as a result of this automation.